2018
DOI: 10.1002/lipd.12112
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous (Pomegranate Juice) or Endogenous (Paraoxonase1) Antioxidants Decrease Triacylglycerol Accumulation in Mouse Cardiovascular Disease‐Related Tissues

Abstract: The polyphenol‐rich pomegranate juice (PJ) and the high‐density lipoprotein (HDL)‐associated paraoxonase1 (PON1) are known as potent atheroprotective antioxidants, but their effects on other tissues related to cardiovascular disease (CVD) remain unknown. The current study aimed to investigate the effects of treating mice with PJ or recombinant PON1 (rePON1) on the oxidation and lipid status of CVD‐related tissues: serum, aorta, heart, liver, kidney, visceral, and subcutaneous adipose tissues (VAT and SAT). Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…PON1 is an enzyme carried in plasma by HDL that confers to these lipoproteins most of their antioxidant properties [17,34]. PON1 was improved after MiPo, but the activity remains constant during the postprandial period, either before or after the supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PON1 is an enzyme carried in plasma by HDL that confers to these lipoproteins most of their antioxidant properties [17,34]. PON1 was improved after MiPo, but the activity remains constant during the postprandial period, either before or after the supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are therapies focused on improving HDL quality and functionality that include the use of functional foods. In vitro and in vivo studies have demonstrated that pomegranate juice reduced the plasma total cholesterol, triglycerides and low-density lipoprotein-cholesterol (LDL-C) levels, and particularly induced an increase in HDL-C plasma levels and serum PON1 activity [14,15,16,17]. These properties have been attributed to pomegranate compounds such as polyphenols, anthocyanins, ellagitannins and punicic acid [18], which should be absorbed and transported, probably by HDL, in plasma during the postprandial state.…”
Section: Introductionmentioning
confidence: 99%
“…Our glycine-based treatment reduces atherosclerosis in mice independent of circulating lipids by enhancing the antioxidant, GSH. Previous studies demonstrated the antiatherogenic and cardioprotective properties of antioxidant interventions [ 42 , 46 , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. For instance, the antioxidant Probucol reduced atheromas and plasma cholesterol in Watanabe heritable hyperlipidemic (WHHL) rabbits due to reductions in modified LDL [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estudios in vitro e in vivo han demostrado que el jugo de la granada reduce los niveles plasmáticos de colesterol total, triglicéridos y LDL, y aumenta los niveles de HDL y la actividad de la PON1; estas propiedades han sido atribuidas al contenido de compuestos bioactivos, los cuales probablemente son absorbidos y transportados por las HDL 28 .…”
Section: Efecto Del Fruto De La Granada Sobre La Pon1unclassified